Menghargai Seperti Yesus Menghargai: Studi Reflektif Markus 12:41-44 Dan Pengorbanan Single Mom Dalam Mengasuh Anak Berkebutuhan Khusus - Meyrlin Saefatu (Sekolah Tinggi Teologi Aletheia, 2025)
This study aims to explore the forms of sacrifice made by single mothers in raising children with special needs (CWSN), drawing theological inspiration from the story of the poor widow in Mark 12:41–44. This biblical narrative represents the values of sincerity and sacrifice, which can strengthen the psychosocial resilience of single mothers facing the challenges of parenting without a partner’s support. A theological and social approach is employed to analyze how spiritual values found in the Bible serve as a source of inner strength and a moral foundation in caregiving practices. The study highlights the construction of resilience through the internalization of religious values and daily life experiences, as well as the significance of sacrifices that encompass material, emotional, and spiritual aspects. The findings indicate that the sacrifices of single mothers, like the widow’s offering, are not measured by their material amount but by their sincerity and transformative impact. Selfless acts for the well-being of CWSN reflect deep love and active faith, becoming a tangible expression of transformative spiritual love. Although often socially unseen, such sacrifices carry profound theological meaning and contribute significantly to the improvement of the child’s quality of life.